(untitled) (Global Conference on Medical and Health Sciences, 2026)
Mitochondrial dysfunction has emerged as a central pathological mechanism underlying a wide range of neurological disorders, including Alzheimer’s disease, Parkinson’s disease, stroke, and amyotrophic lateral sclerosis. As the primary source of cellular energy and a key regulator of metabolic homeostasis, mitochondria play a critical role in maintaining neuronal function and survival. Disruption of mitochondrial dynamics, bioenergetics, and signaling pathways leads to impaired energy production, increased oxidative stress, and activation of cell death pathways.